A Thirteen-Year Analysis of Facial Fractures among Professional Soccer Players - Kozlowski, Konrad M.; Rosston, Peter A.; Park, Asher C.; Hakimi, Amir A.; Socolovsky, Leandro; Wong, Brian J-F (Facial Plastic Surgery, 2023)
This study aims to identify the epidemiology and effects of facial fractures on return to play (RTP) in Major League Soccer (MLS) and the English Premier League (EPL). A total of 39 MLS players and 40 EPL players who sustained facial fractures from 2007 to 2019 were identified. Data on player demographics, the injury, and the impact of their injury on RTP were collected. Elbow-to-head was the most common mechanism of injury (20.3%). The most common fracture involved the nasal bone (48.3%). Most players (90%) RTP the same season. Players who sustained nasal fractures missed significantly fewer games (p < 0.001) than those who suffered other craniofacial fractures. Players treated surgically missed significantly more games (3.21 vs. 0.71, p = 0.006) and days (30.1 vs. 8.70, p = 0.002) than those managed nonoperatively. Significantly more EPL players who sustained facial fractures wore headgear upon RTP compared to MLS players (82% vs. 56%, p <0 .01). Most professional soccer players who sustain a facial fracture RTP the same season, but their recovery time can vary depending on the type of fracture, injury management, or injury severity. Our findings can help inform future craniofacial injury management as well as guidelines on player safety and fracture prevention.
Keywords: facial fracture; soccer; sport injury; fracture management; return to play